Peran Badan Kesatuan Bangsa Dan Politik Dalam Pelayanan Perizinan Permohonan Rekomendasi Penelitian Di Kabupaten Sidoarjo - Mustika Amalia, Nadila; Prathama, Ananta (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Quality public services are one of the pillars of good governance, including research licensing in Indonesia. The Sidoarjo District National and Political Unity Agency (Bakesbangpol) has a strategic role in managing and providing licensing recommendations for research conducted in the region. The licensing process is often challenging for researchers due to their limited understanding of the procedures and requirements that must be met. Therefore, Bakesbangpol needs to provide transparent, accountable and responsive services so that researchers can easily obtain the necessary recommendations. This study aims to analyze the role of Bakesbangpol in research recommendation licensing services and the challenges faced in the process. The research method used is descriptive qualitative with a literature study approach, observation, interviews, and documentation. The results showed that Bakesbangpol functions as a liaison between researchers and the local government, and is responsible for ensuring that the research conducted does not disturb public order and is in accordance with regional policies. However, the challenges faced include complicated bureaucracy, lack of socialization on procedures, and limited human resources. Efforts to improve service quality can be made through digitization, training, and better socialization to researchers. Thus, Bakesbangpol can contribute more effectively to the development of research in Sidoarjo Regency.